Black & blue: a journey through the lens of an unapologetic black female officer - Wright, Lanah (Lanah Wright, 2024)
Lanah Wright is not only an officer who has served her community for over seven years, but an African American woman, who has navigated the challenging territory of law enforcement with courage and dedication. Wright holds a Master of Arts in International Crime from John Jay College of Criminal Justice. Her background has equipped her with an understanding of the societal issues that often intersect with policing. Wright gives an unflinching account of her experiences, with a personal touch of humor. This book is not just for those interested in policing, but anyone seeking to understand the complexities of serving as a minority in law enforcement